Justice league unlimited Saving the world. - DC Comics, Inc.; Warner Bros. Entertainment; Warner Home Video (Firm).; Warner Home Video (Phils.) Inc. (Burbank, Calif. Manufactured and distributed by Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils.) Inc., 2005)
Under the leadership of the original Justice League, Earth's superheroes band together to form an unbeatable force that's always ready for action! These three exciting adventures from the hit TV show feature battles with a menacing nuclear robot, the egomaniacal child magician Mordred and the dangerous god of war Ares. In Justice League Unlimited, there's always a hero around when you need one!
Voices: Carl Lumbly, Phil LaMarr, George Newbern, Kevin Conroy, Kin Shriner, Susan Eisenberg, Olivia d'Abo, Soren Fulton, Jason Hervey, Fred Savage.
MPAA rating: Not rated.
VCD
Keywords: Good and evil -- Drama; Heroes -- Juvenile drama